Lingonberry Improves Hepatic Lipid Metabolism by Targeting Notch1 Signaling - Susara Madduma Hewage; Kathy K. W. Au-Yeung; Suvira Prashar; Charith U. B. Wijerathne; Karmin O; Yaw L. Siow (MDPI AG, 2022)
Impaired hepatic lipid metabolism is a hallmark of non-alcoholic fatty liver disease (NAFLD), which has no effective treatment option. Recently, Notch signaling has been identified as an important mediator of hepatic lipid metabolism. Lingonberry (Vaccinium vitis-idaea L.) is an anthocyanin-rich fruit with significant lipid-lowering properties. In this study, we examined how lingonberry influenced Notch signaling and fatty acid metabolism in a mouse model of NAFLD. Mice (C57BL/6J) fed a high-fat diet (HFD) for 12 weeks developed fatty liver and activated hepatic Notch1 signaling. Lingonberry supplementation inhibited hepatic Notch1 signaling and improved lipid profile by improving the expression of the genes involved in hepatic lipid metabolism. The results were verified using a palmitic-acid-challenged cell model. Similar to the animal data, palmitic acid impaired cellular lipid metabolism and induced Notch1 in HepG2 cells. Lingonberry extract or cyanidin-3-glucoside attenuated Notch1 signaling and decreased intracellular triglyceride accumulation. The inhibition of Notch in the hepatocytes attenuated sterol-regulatory-element-binding-transcription-factor-1 (SREBP-1c)-mediated lipogenesis and increased the expression of carnitine palmitoyltransferase-I-alpha (CPTIα) and acyl-CoA oxidase1 (ACOX1). Taken together, lingonberry's hepatoprotective effect is mediated by, in part, improving hepatic lipid metabolism via inhibiting Notch1 signaling in HFD-induced fatty liver.